Acid pickling method of titanium alloy implant material

By using a specific ratio pickling solution and ultrasonic cleaning step, the sheet-like oxide layer of the titanium alloy implant material is removed to form a passivation film with high corrosion resistance, solving the corrosion resistance of titanium alloy implant material in oral applications. The problem of insufficient improvements in the oral environment.

CN119121247APending Publication Date: 2024-12-13BEIJING CARLS MEDICAL EQUIPMENT CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411270724.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The sheet-like oxide layer generated by titanium alloy implant materials during processing reduces its corrosion resistance and mechanical properties, making it difficult to meet the needs of the oral clinical environment.

Method used

The titanium alloy implanted material was pickled for 80-150 seconds using HF, HNO3 and water at a volume ratio of (3-10): (3-10): 120 to remove the sheet layer and form a resistance to resistance. A highly corrosive titanium dioxide passivation film, combined with ultrasonic cleaning steps to ensure surface cleaning.

Benefits of technology

It significantly improves the hydrophilicity and corrosion resistance of titanium alloy implanted materials, reduces surface pitting phenomenon, and meets the use needs of the oral clinical environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005038617320000041
    Figure BDA0005038617320000041
  • Figure BDA0005038617320000051
    Figure BDA0005038617320000051
  • Figure BDA0005038617320000061
    Figure BDA0005038617320000061
Patent Text Reader

Abstract

The invention relates to the technical field of titanium alloy material surface treatment processes, and particularly discloses a pickling method for a titanium alloy implant material. The pickling method of the titanium alloy implant material comprises the following steps that a pickling solution is prepared, specifically, HF, HNO3 and water are mixed according to the volume ratio of (3-10): (3-10): 120 and stirred to be uniform, and the pickling solution is obtained; and acid pickling is conducted, specifically, the titanium alloy implant material is soaked in an acid pickling solution, timing is started when the titanium alloy implant material is completely soaked in the acid pickling solution, and the acid pickling time is controlled to be 80-150 s. According to the pickling method for the titanium alloy implant material, a flaky oxide layer on the surface of the titanium alloy implant material can be effectively removed, meanwhile, the surface pitting phenomenon is reduced, and the hydrophilicity and corrosion resistance of the titanium alloy implant material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of titanium alloy material surface treatment, and in particular to a pickling method for titanium alloy implant materials. Background Art

[0002] Ti-6Al-4V titanium alloy has been widely used in the field of medical devices due to its excellent biocompatibility, high mechanical strength, low density and excellent corrosion resistance. Especially in stomatology, titanium alloy is an important component of implants and abutments, and its performance directly affects the long-term stability of implants and the oral health of patients. In recent years, a large number of studies have shown that during the machining of alloys, a recast layer will be produced on the surface of the alloy. Due to the high temperature, the molten material will oxidize and deposit on the surface of the recast layer as a flaky layer with a thickness of about 4-9μm when cooled. The flaky layer contains pollutants and oxides. The presence of this flaky layer will reduce the corrosion resistance and mechanical properties of titanium alloys, causing poor bone integration of titanium alloy implants and leading to implant failure.

[0003] As an important pre-treatment method, pickling is simple to operate, the process is controllable, and the price is low. It can effectively remove the oxide layer, oil stains and impurities on the surface of titanium alloys, and provide a clean and uniform substrate surface for other subsequent surface treatment processes. At present, titanium alloy materials are mostly used in the aerospace field, and their pickling is usually carried out under high temperature and high concentration conditions. However, the hydrophilicity and corrosion resistance of the titanium alloy surface obtained under the above pickling conditions are poor, which makes it difficult for titanium alloy implant materials to meet the use requirements of the oral clinical environment.

[0004] Therefore, it is necessary to study a pickling method for surface decontamination, increasing hydrophilicity and corrosion resistance of titanium alloy implantable biomaterials. Summary of the invention

[0005] In order to remove the flaky oxide layer on the surface of titanium alloy implant materials, reduce surface pitting, and improve hydrophilicity and corrosion resistance, the present application provides a pickling method for titanium alloy implant materials.

[0006] The pickling method of titanium alloy implant material provided in this application adopts the following technical scheme: A method for pickling a titanium alloy implant material comprises the following steps: Prepare pickling solution: mix HF, HNO3 and water in a volume ratio of (3-10): (3-10): 120, stir evenly, and obtain pickling solution; Pickling: Immerse the titanium alloy implant material in the pickling solution. Start timing from when the titanium alloy implant material is completely immersed in the pickling solution. The pickling time is controlled within 80-150s.

[0007] The present application provides a pickling method for titanium alloy implant materials. The pickling method uses the pickling solution of the above-mentioned specific ratio for pickling, and controls the pickling time between 80-150s. It can evenly remove the flaky layer that appears on the surface of the titanium alloy after machining, and obtain a titanium alloy implant material with good surface hydrophilicity, less surface pitting and high corrosion resistance.

[0008] The inventor of this application found that after pickling the titanium alloy implant material using the pickling method provided by this application, the corrosion resistance of the titanium alloy implant material is enhanced. The reason for the analysis is that HNO3 in the pickling solution can react on the surface of the titanium alloy implant material and form a titanium dioxide passivation film, which has good corrosion resistance. Therefore, the corrosion resistance of the titanium alloy implant material after pickling is significantly improved. Regarding the concentration of the pickling solution provided by this application, the inventor found through experimental exploration that the concentration of HF or HNO3 in the pickling solution will affect the hydrophilicity and corrosion resistance of the titanium alloy implant material; specifically, when the concentration of HF or HNO3 is low, the pickling solution can only show slight corrosion on the surface of the titanium alloy implant material; when the concentration of HNO3 is high, it will cause excessive growth of the titanium dioxide passivation film, affecting the performance of the titanium alloy implant material; only when the concentration of HF and HNO3 in the pickling solution is controlled within the above range, on the one hand, a passivation film is formed on the surface of the titanium alloy implant material, so that the corrosion resistance is improved; on the other hand, different micro-nano structures and morphologies can be produced on the surface of the sample, thereby indirectly improving the hydrophilicity of the titanium alloy implant material.

[0009] In some embodiments, the volume ratio of HF, HNO3 and water can be (3-4): 5:120, (3-5): 5:120, (3-8): 5:120, (3-10): 5:120, (4-5): 5:120, (4-8): 5:120, (4-10): 5:120, (5-8): 5:120, (5-10): 5:120 , (8-10): 5: 120, 5: (3-4): 120, 5: (3-5): 120, 5: (3-8): 120, 5: (3-10): 120, 5: (4-5): 120, 5: (4-8): 120, 5: (4-10): 120, 5: (5-8): 120, 5: (5-10): 120 or 5: (8-10): 120.

[0010] In a specific embodiment, the volume ratio of HF, HNO3 and water can also be 3:5:120, 4:5:120, 5:5:120, 8:5:120, 10:5:120, 5:3:120, 5:4:120, 5:8:120 or 5:10:120.

[0011] Optionally, the volume ratio of HF, HNO3 and water is (4-8): (4-8): 120.

[0012] In the present application, it was found through experimental research that by further controlling the volume ratio of HF, HNO3 and water within the above range, the hydrophilicity and corrosion resistance of the titanium alloy implant material obtained by pickling are better.

[0013] Optionally, the volume ratio of HF, HNO3 and water is 5:5:120.

[0014] In this application, the inventors conducted an experimental study on the pickling rate of the above-mentioned pickling solution and found that the amount of titanium alloy implant surface removed was linearly related to the pickling time (e.g. Figure 6 As shown), the cleaning rate of the pickling solution with the above ratio is 0.064 μm / s. Therefore, the present application further controls the volume ratio of HF, HNO3 and water to 5:5:120, and the obtained pickling solution can remove the flaky layer on the surface of the titanium alloy implant material at a uniform speed, and the flaky layer on the surface of the titanium alloy implant material can be completely removed by adjusting the pickling time.

[0015] Optionally, the temperature of the pickling solution is 25-28°C.

[0016] Optionally, the pickling method of the titanium alloy implant material also includes post-processing, and the specific steps are: after the pickling is completed, the titanium alloy implant material is placed in a deionized water tank for ultrasonic cleaning, and the frequency of ultrasonic cleaning is 30-110 Hz and the time is 240-720s.

[0017] In the present application, by ultrasonically cleaning the titanium alloy implant material after pickling, the pickling liquid on the surface of the titanium alloy implant material can be effectively removed, thereby avoiding the influence of the residual pickling liquid on the hydrophilicity and corrosion resistance of the titanium alloy implant material surface.

[0018] Optionally, the ultrasonic cleaning is divided into two times, the first ultrasonic cleaning has a frequency of 30-50 Hz and a duration of 240-360 s, and the second ultrasonic cleaning has a frequency of 90-110 Hz and a duration of 240-360 s.

[0019] In this application, it was found through experimental research that further adopting a two-step ultrasonic cleaning process can make the pickling solution removed more thoroughly, and the hydrophilicity and corrosion resistance of the titanium alloy implant material better.

[0020] In some embodiments, the frequency of the first ultrasonic cleaning is 30-40 Hz or 40-50 Hz. In a specific embodiment, the frequency of the first ultrasonic cleaning is 30 Hz, 40 Hz, or 50 Hz.

[0021] In some embodiments, the frequency of the second ultrasonic cleaning is 90-100 Hz or 100-110 Hz.

[0022] In a specific embodiment, the frequency of the second ultrasonic cleaning is 90 Hz, 100 Hz, or 110 Hz.

[0023] Optionally, the frequency of the first ultrasonic cleaning is 40 Hz, and the time is 300 s, and the frequency of the second ultrasonic cleaning is 100 Hz, and the time is 300 s.

[0024] In summary, this application has the following beneficial effects: 1. The present application provides a pickling method for titanium alloy implant materials, which uses HF, HNO3 and water in a volume ratio of (3-10): (3-10): 120 as a pickling solution. The titanium alloy implant material is pickled using the above pickling solution, which can effectively remove the flaky layer on the surface of the titanium alloy implant material, reduce pitting corrosion, and improve the hydrophilicity and corrosion resistance of the titanium alloy implant material.

[0025] 2. The post-processing step of the present application further adopts two ultrasonic cleanings. By controlling the frequency and time of the two ultrasonic cleanings within the following ranges: the frequency of the first ultrasonic cleaning is 30-50kHz, the time is 240-360s, and the frequency of the second ultrasonic cleaning is 90-110kHz, the time is 240-360s, the surface hydrophilicity of the obtained titanium alloy implant material is better and the corrosion resistance is better. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is a flow chart of the pickling method of titanium alloy implant material provided by the present application; Figure 2 is a metallographic microscope image of an untreated titanium alloy implant material and a titanium alloy implant material treated in Example 3; Figure 3 is an electron microscope image of an untreated titanium alloy implant material and a titanium alloy implant material treated in Example 3; Figure 4 is a fitting diagram of the contact angles of an untreated titanium alloy implant material and a titanium alloy implant material treated in Example 3; Figure 5 1 is a polarization curve diagram of an untreated titanium alloy implant material and a titanium alloy implant material treated in Example 3; Figure 6 This is the regression curve of the change of single-side removal amount of titanium alloy implant material by the pickling solution of Preparation Example 3 over time. DETAILED DESCRIPTION

[0027] The present application provides a method for pickling a titanium alloy implant material, comprising the following steps: (1) preparing pickling solution: mixing HF, HNO3 and water in a volume ratio of (3-10): (3-10): 120, stirring evenly at 25-28° C. to obtain pickling solution; transferring the pickling solution to a polytetrafluoroethylene tank using a special acid pump. Furthermore, the volume ratio of HF, HNO3 and water is (4-8): (4-8): 120.

[0028] (2) Pickling: Conduct material inspection on the titanium alloy implants to be produced. Place the titanium alloy implant materials that have passed the inspection in a titanium basket to avoid contact and overlap. Place the titanium basket in the trough and ensure that the titanium alloy implant materials are completely immersed in the pickling solution. Slightly shake the titanium basket. Start timing from the time the titanium alloy implant materials are completely immersed in the pickling solution. The pickling time is controlled at 80-150s.

[0029] (3) Post-treatment: After pickling, the titanium basket is immediately taken out and placed in two deionized water tanks for ultrasonic cleaning. The power of the first ultrasonic cleaning is 80-100 W, and the power of the second ultrasonic cleaning is 25-40 W. The time of both ultrasonic cleanings is 30±10 s. After cleaning, the titanium alloy implant material is placed in deionized water for storage.

[0030] In the present application, the titanium alloy implant material is Ti-6Al-4V titanium alloy rod purchased from Sap Precision Metal (Taicang) Co., Ltd., and HF and HNO3 are purchased from Xilong Science Co., Ltd.; the raw materials, reagents, solvents, etc. used in this application can all be obtained commercially.

[0031] The present application is further described in detail below in combination with preparation examples, embodiments, performance testing experiments and accompanying drawings.

[0032] Preparation Example 1-9 Preparation Examples 1-9 each provide an acid wash solution.

[0033] The difference between the above preparation examples is that the volume ratios of HF, HNO3 and water in the pickling solution are specifically shown in Table 1 below.

[0034] The preparation method of the pickling solution provided in Preparation Example 1-9 is: HF, HNO3 and water are mixed in a certain volume ratio, and stirred evenly at 25°C to obtain the pickling solution.

[0035] Table 1 Volume ratio of HF, HNO3 and water in the pickling solution provided in Preparation Examples 1-9 Comparative Preparation Example 1 Comparative Preparation Example 1 provides an acid wash solution.

[0036] The difference between the above preparation examples is that the volume ratio of HF, HNO3 and water in the pickling solution is 6:60:100.

[0037] Comparative Preparation Example 2 Comparative Preparation Example 2 provides an acid wash solution.

[0038] The difference between the above preparation examples is that the volume ratio of HF, HNO3 and water in the pickling solution is 15:95:110.

[0039] Comparative Preparation Example 3 Comparative Preparation Example 3 provides an acid wash solution.

[0040] The difference between the above preparation examples is that the volume ratio of HF, HNO3 and water in the pickling solution is 15:15:120.

[0041] Examples 1-9 Examples 1-9 respectively provide a method for pickling a titanium alloy implant material.

[0042] The difference between the above embodiments is that in the pickling method of titanium alloy implant material, the pickling liquids are respectively derived from Preparation Examples 1-9.

[0043] The pickling method of the titanium alloy implant material provided in Examples 1-9 comprises the following steps: (1) Preparation of pickling solution: Prepare according to Preparation Examples 1-9 respectively.

[0044] (2) Pickling: Conduct material inspection on the titanium alloy implants to be produced. Place the titanium alloy implant materials that have passed the inspection in a titanium basket to avoid contact and overlap. Place the titanium basket in the trough and ensure that the titanium alloy implant materials are completely immersed in the pickling solution. Slightly shake the titanium basket. Start timing from the moment the titanium alloy implant materials are completely immersed in the pickling solution. The pickling time is controlled at 90-95s.

[0045] (3) Post-treatment: After the pickling is completed, the titanium basket is immediately taken out and the titanium alloy implant material is placed in a deionized water tank for ultrasonic cleaning. The frequency of ultrasonic cleaning is 110 kHz and the time is 600 s. After cleaning, the titanium alloy implant material is placed in deionized water for storage.

[0046] Example 10 Example 10 provides a method for pickling a titanium alloy implant material.

[0047] The difference between the above embodiment and embodiment 3 is that the ultrasonic cleaning frequency is 40 kHz and the time is 600 s.

[0048] Examples 11-21 Examples 11-21 respectively provide a method for pickling a titanium alloy implant material.

[0049] The difference between the above embodiment and embodiment 3 is that the ultrasonic cleaning is divided into two times, and the titanium alloy implant material after acid washing is placed in two deionized water tanks for ultrasonic cleaning in turn. The frequency and time of the two ultrasonic cleanings are shown in Table 2 below.

[0050] Table 2 Frequency and time of ultrasonic cleaning in the pickling method of Examples 11-21 Comparative Examples 1-3 Comparative Examples 1-3 respectively provide a pickling method for a titanium alloy implant material.

[0051] The difference between the above comparative example and Example 3 is that in the pickling method of the titanium alloy implant material, the pickling liquids are derived from comparative preparation examples 1-3 respectively.

[0052] Performance testing The titanium alloy implant materials obtained after pickling in Examples 1-21 and Comparative Examples 1-3 were tested, and the results are shown in Table 3 below.

[0053] (1) Surface state: The surface state of the titanium alloy implant material of Example 3 before and after pickling was observed using a metallographic microscope and an electron microscope. Figure 2 (A) is a metallographic microscope image of an untreated titanium alloy implant material; Figure 2 (B) is a metallographic microscope image of the titanium alloy implant material after treatment in Example 3; Figure 3 (A) is an electron microscope image of an untreated titanium alloy implant material; Figure 3 (B) is an electron microscope image of the titanium alloy implant material after treatment in Example 3.

[0054] (2) Hydrophilicity: A contact angle meter was used to measure the water contact angle α of the untreated titanium alloy implant material and the titanium alloy implant materials obtained after pickling in Examples 1-21 and Comparative Examples 1-3. Five random locations were tested and the average value was taken. Figure 4 (A) is the contact angle fitting diagram of untreated titanium alloy implant material; Figure 4 (B) is the contact angle fitting diagram of the titanium alloy implant material after treatment in Example 3.

[0055] (3) Corrosion resistance: The corrosion resistance of the untreated titanium alloy implant material and the titanium alloy implant material obtained after pickling in Examples 1-21 and Comparative Examples 1-3 was tested using a CHI760E electrochemical workstation to obtain polarization curves, and the self-corrosion current was obtained from the polarization curves; and it was observed whether there was an obvious situation where the corrosion current remained unchanged and the corrosion voltage suddenly increased. Figure 5 (A) is the polarization curve of untreated titanium alloy implant material; Figure 5(B) is a polarization curve diagram of the titanium alloy implant material after treatment in Example 3; Note: In the polarization curve, the smaller the self-corrosion current, the better the corrosion resistance; when the corrosion current remains unchanged and the corrosion voltage suddenly increases in the polarization curve, it indicates that there is a passivation film resistance on the surface of the titanium alloy implant material.

[0056] Table 3 Performance test results of titanium alloy implant materials of Examples 1-21 and Comparative Examples 1-3 According to the test results in Table 3, the surface contact angle of the titanium alloy implant material treated by the pickling method of the titanium alloy implant material provided in Examples 1-21 is 46.18-54.38°, and the self-corrosion current is -9.4 to -9.0 A·cm -2 , and the polarization curve shows that the corrosion current remains unchanged and the corrosion voltage increases suddenly; the surface contact angle of the titanium alloy implant material treated by the pickling method of the titanium alloy implant material provided in Comparative Examples 1-3 is 62.49-70.53°, and the self-corrosion current is -9.0~-8.7A·cm -2 , and the polarization curve also shows that the corrosion current remains unchanged and the corrosion voltage increases suddenly; while the surface contact angle of the untreated titanium alloy implant material is 89.42°, and the self-corrosion current is -8.5A·cm -2 , and the polarization curve does not show a situation where the corrosion current remains unchanged and the corrosion voltage suddenly increases. Therefore, it is shown that the hydrophilicity of the titanium alloy implant material treated by the pickling method of the titanium alloy implant material provided by Examples 1-21 is significantly improved, and the pickling method forms a passivation film on the surface of the titanium alloy implant material, and the titanium alloy implant material has high corrosion resistance.

[0057] The test results of Examples 1-9 and Comparative Examples 1-3 show that the contact angle of the titanium alloy implant material obtained in Examples 1-9 is 47.63-54.38° (<55°), and the self-corrosion current is -9.3 to -9.0 A·cm -2 , while the contact angle of the titanium alloy implant material obtained in Comparative Examples 1-3 is 62.49-70.53°, and the self-corrosion current is -9.0~-8.8A·cm -2 , indicating that the volume ratio of HF, HNO3 and water in the pickling solution is controlled within the range of (3-10): (3-10): 120 in this application, and the titanium alloy implant material obtained by pickling has good hydrophilicity and excellent corrosion resistance.

[0058] Further comparison of the test results of Examples 1-9 revealed that, with the increase of HF concentration or HNO3 concentration in the pickling solution, the contact angle of the titanium alloy implant material obtained showed a trend of first decreasing and then increasing, and the self-corrosion current showed a trend of first increasing and then decreasing; further comparison revealed that the contact angle of the titanium alloy implant material obtained in Examples 2-4 and Examples 7-8 was 47.63-49.96° (<50°), and the self-corrosion current was -9.3 to -9.2 A·cm -2 , while the contact angles of the titanium alloy implant materials obtained in Examples 1, 5-6, and 9 were 50.37-54.38°, and the self-corrosion current was -9.1 to -9.0 A·cm -2 Therefore, it is explained that the present application further controls the volume ratio of HF, HNO3 and water in the pickling solution within the range of (4-8): (4-8): 120, and the titanium alloy implant material obtained by pickling has better hydrophilicity and better corrosion resistance.

[0059] The test results of Example 3 and Example 10-21 show that Example 3 and Example 10 use one ultrasonic cleaning, and the contact angle of the titanium alloy implant material obtained is 47.63-49.83°; while Example 11-21 uses two ultrasonic cleanings, and the contact angle of the titanium alloy implant material obtained is 46.18-47.32°. Therefore, it is shown that the two-step cleaning used in this application can fully remove the pickling solution on the surface of the titanium alloy implant material and improve the hydrophilicity of the titanium alloy implant material.

[0060] Further comparison of the test results of Examples 11-21 shows that the contact angle of the titanium alloy implant material obtained in Example 11-19 is 46.21-46.96° (<47°); while the contact angle of the titanium alloy implant material obtained in Example 20-21 is 47.19-47.32°. Therefore, it is explained that the present application further controls the frequency and time of the two ultrasonic cleanings within the following range: the frequency of the first ultrasonic cleaning is 30-50kHz, the time is 240-360s, and the frequency of the second ultrasonic cleaning is 90-110kHz, the time is 240-360s, which can make the pickling liquid on the surface of the titanium alloy implant material more thoroughly removed, and the hydrophilicity of the titanium alloy implant material is better.

[0061] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A method for pickling a titanium alloy implant material, characterized in that: The following steps are involved: Prepare pickling solution: mix HF, HNO3 and water in a volume ratio of (3-10): (3-10): 120, stir evenly, and obtain pickling solution; Pickling: Immerse the titanium alloy implant material in the pickling solution. Start timing from when the titanium alloy implant material is completely immersed in the pickling solution. The pickling time is controlled within 80-150s.

2. The pickling method of titanium alloy implant material according to claim 1, characterized in that: The volume ratio of HF, HNO3 and water is (4-8): (4-8):

120.

3. The pickling method of titanium alloy implant material according to claim 1, characterized in that: The volume ratio of HF, HNO3 and water is 5:5:

120.

4. The pickling method of titanium alloy implant material according to claim 1, characterized in that: The temperature of the pickling solution is 25-28°C.

5. The pickling method of titanium alloy implant material according to claim 1, characterized in that: The pickling method of the titanium alloy implant material also includes post-processing, and the specific steps are: after the pickling is completed, the titanium alloy implant material is placed in a deionized water tank for ultrasonic cleaning, and the frequency of the ultrasonic cleaning is 30-110 Hz and the time is 240-720s.

6. The pickling method of titanium alloy implant material according to claim 1, characterized in that: The ultrasonic cleaning is divided into two times, the first ultrasonic cleaning frequency is 30-50 Hz, the time is 240-360 s, and the second ultrasonic cleaning frequency is 90-110 Hz, the time is 240-360 s.

7. The pickling method of titanium alloy implant material according to claim 1, characterized in that: The frequency of the first ultrasonic cleaning is 40 Hz, and the time is 300 s, and the frequency of the second ultrasonic cleaning is 100 Hz, and the time is 300 s.

8. A titanium alloy implant material obtained by the pickling method of a titanium alloy implant material according to any one of claims 1 to 8, characterized in that: The surface contact angle of the titanium alloy implant material after pickling is ≤50°.

Citation Information

Cited By

  • Sand blasting method for pure titanium implant material and sand-blasted pure titanium implant material

    CN120382431A